Penile reconstruction with dermal template and vacuum therapy in severe skin and soft tissue defects caused by Fournier's gangrene and hidradenitis suppurativa - Ludolph, Ingo (Int Wound J, 2014)
The aim of this article is to improve the treatment of patients with complete skin loss of the penile shaft after Fournier's gangrene or hidradenitis suppurativa using modern biomatrices and topical negative pressure therapy. From January 2010 to December 2011, three patients with Fournier's gangrene or hidradenitis suppurativa were treated. After initial radical debridements, topical negative pressure therapy was applied for wound stabilisation. After that dermal templates (acellular dermal matrix) were used to achieve early healing and topical negative pressure‐dressing in a special setting or a special foam compression bandage was used together with a urinary catheter. After integration of the dermal template, a split‐thickness skin graft is used for coverage and again secured with a circular total negative pressure‐dressing. In all cases, the split‐thickness skin grafts healed very well applying this therapy concept. The patients were very satisfied with the functional as well as with the aesthetic outcome. We suggest a new method of staged reconstruction to successfully preserve the functionality of the penis after complete loss of the skin and soft tissue of the penile shaft using modern biomatrices and topical negative pressure therapy.